2011
DOI: 10.1111/j.1365-2435.2011.01942.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental immune history affects adult immune function but not carotenoid‐based ornamentation in mallard ducks

Abstract: Summary1. Sexually selected traits often honestly advertise aspects of individual quality, such as immune function. Such traits have traditionally been thought to reveal real-time information (e.g. current health state), but they may also reflect immunological conditions experienced during ontogeny, which can fundamentally shape survival prospects, adult immune function, and reproductive performance. 2. We tested the effects of immune challenges (injections of sheep red blood cells) during neonatal development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 80 publications
(160 reference statements)
0
19
0
Order By: Relevance
“…We acquired 46 one‐day‐old female ducklings from Metzer Farms (Gonzales, CA, USA) in December 2009 and housed them as in Butler & McGraw (, ). Ducklings were reared indoors in randomly selected groups of five ducklings per cage (60 × 60 × 60 cm) until they were 2 weeks old, then three per cage until they were 4 weeks old, and then two per cage until they were 7 weeks old, at which point all birds were moved outside and individually housed to allow for normal sexual maturation (Butler & McGraw , ). Light : dark regime was 13L : 11D when ducklings were housed indoors, and natural photoperiod thereafter (10·5L : 13·5D at 7 weeks old to 13·5L : 10·5D at 20 weeks old).…”
Section: Methodsmentioning
confidence: 99%
“…We acquired 46 one‐day‐old female ducklings from Metzer Farms (Gonzales, CA, USA) in December 2009 and housed them as in Butler & McGraw (, ). Ducklings were reared indoors in randomly selected groups of five ducklings per cage (60 × 60 × 60 cm) until they were 2 weeks old, then three per cage until they were 4 weeks old, and then two per cage until they were 7 weeks old, at which point all birds were moved outside and individually housed to allow for normal sexual maturation (Butler & McGraw , ). Light : dark regime was 13L : 11D when ducklings were housed indoors, and natural photoperiod thereafter (10·5L : 13·5D at 7 weeks old to 13·5L : 10·5D at 20 weeks old).…”
Section: Methodsmentioning
confidence: 99%
“…We have described these challenges in detail elsewhere [52], [55], so here we briefly review our methodologies.…”
Section: Methodsmentioning
confidence: 99%
“…We quantified total carotenoid titer (predominately lutein and zeaxanthin; [55]) for all individuals at the beginning and end of DEV, the beginning of ADULT, and on D0, D1, D6, and D10 of the adult immune assessment period.…”
Section: Methodsmentioning
confidence: 99%
“…If CORT can lead to a reduction in beak coloration (sensu McGraw et al 2011), highquality males may have the ability to buffer against increases in circulating CORT. Butler and McGraw (2012b) found that baseline bill saturation in mallards (Anas platyrhynchos) was positively correlated with their cutaneous immune response, although they failed to find a relationship between Ab levels in response to KLH challenge and aspects of bill color or circulating carotenoid levels. Faivre et al (2003) demonstrated that blackbirds (Turdus merula) challenged with sheep red blood cells (SRBCs) exhibited a rapid decline in yellow coloration, but that, in contrast to our findings, the likelihood of becoming duller was positively linked to the strength of anti-SRBC response.…”
Section: )mentioning
confidence: 96%
“…Faivre et al (2003) demonstrated that blackbirds (Turdus merula) challenged with sheep red blood cells (SRBCs) exhibited a rapid decline in yellow coloration, but that, in contrast to our findings, the likelihood of becoming duller was positively linked to the strength of anti-SRBC response. The yellow coloration of the blackbird and mallard beaks is dependent upon carotenes and zeaxanthins (blackbird: Faivre et al 2003), and xanthophylls and zeaxanthins (mallards (Butler and McGraw 2012b), and is not dependent upon ketocarotenoids as is beak coloration in zebra finches. The yellow beak may represent more basic components of resource acquisition (Hill 2002), rather than processes related to metabolic efficiency (Hill 2014;Ge et al 2015).…”
Section: )mentioning
confidence: 97%